The Symbolic Meaning of Ulos in Batak Culture Indentity: A Weaving Tradition Perspective - Jekmen Sinulingga; Rahel Theresia Rodame Situmorang; Tifany (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to uncover the symbolic meaning of ulos in the formation of Batak cultural identity through the perspective of the weaving tradition. Using a qualitative approach with text analysis, this study examines weavers' narratives, cultural documents, and representations of ulos motifs and structures as cultural texts containing a network of meanings. The analysis is conducted by interpreting the weavers' creative narratives and linking them to the social, aesthetic, and spiritual functions of ulos. The research findings indicate that ulos has layered meanings that reflect ancestral values, kinship relations, and customary legitimacy. It is produced through a creative process rich in personal experience and collective memory. The weaving tradition serves as an important space for the inheritance of cultural values, as weavers act as cultural agents, maintaining the continuity of ulos symbolism amidst social change. The study also found that the meaning of ulos is not only evident in its use in traditional ceremonies but is shaped throughout the process of motif creation through the weavers' reflection of cultural values. This demonstrates that Batak identity is dynamic and continuously negotiated through practices of cultural representation. The limitations of this study lie in the limited scope of informants and the lack of exploration of the meaning of ulos across all Batak sub-ethnicities. Further research is recommended to broaden the perspectives of users and examine the influence of globalization on motif transformation. This study provides theoretical and practical contributions to the preservation of Batak cultural heritage through a deeper understanding of the symbolism of ulos as a living cultural text.